AUDIT ENERGY AS A STUDY ON THE IMPLEMENTATION OF ENERGY MANAGEMENT TO IMPROVE THE EFFICIENCY OF ELECTRICITY USAGE AT FALETEHAN UNIVERSITY - Dewi Anggraini; Robby Mafirli; Tri Winahyu Hariyadi (Journal of Industrial Engineering & Management Research, 2024)
The Government through the Ministry of Energy and Mineral Resources and PT Perusahaan Listrik Negara (PLN Persero) have decided to increase the basic electricity tariff as of July 1, 2022. This certainly impacts the operational costs in the provision of education at Faletehan University. With this increase in operational costs, efforts to improve the efficiency of electricity usage are needed, one of which is through the implementation of energy management in managing electricity usage at Faletehan University. Energy management itself is an integrated activity carried out by an institution to control energy consumption in order to achieve effective and efficient energy utilization to produce maximum output through structured and economical technical measures to minimize energy consumption, as stipulated in Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia No. 14 of 2012. Based on this, research related to the implementation of energy management as an effort to improve the efficiency of electricity usage is needed, with the research location at Faletehan University. This research aims to identify where and how much energy is used by Faletehan University and what steps can be taken to conserve energy as an effort to improve the efficiency of electricity usage at Faletehan University